A Case Study Of Airbus: Overcoming Current Hurdles And Drafting Growth Strategies For The Future - Shan, Neo Sue (2009)
Airbus has a very strong customer base of European legacy airlines, as well as the emerging low cost carriers (LCC). Airbus benefited from its culturally diverse workforce.